848. Trends of Carbapenem Resistance in Enterobacterales in the US Between 2015 and 2019. (31st December 2020) - Marcella, Stephen; Kanakamedala, Hemanth; Zhou, Yun; Cai, Bin; Pogue, Jason M
Abstract: Background: Carbapenem-resistant Enterobacterales (CRE) are considered an urgent threat to human health by the CDC. Tracking resistance over time is of importance to understand trends and patterns. Tracking carbapenem resistance is complicated by definitions which include resistance to ertapenem only which can differ in epidemiology, mechanism, and treatment options. This study examines trends of CRE from 2015 to 2019 and the impact of carbapenem resistance on outcomes. Methods: Enterobacterales infections identified in the Premiere HealthCare database from 2015 to 2019 were categorized into 3 groups: ertapenem only resistant (Erta-R); isolates resistant to ertapenem and class 2 carbapenems (CR-1/2); and carbapenem susceptible (CS). Trends in resistance over the study period were assessed. Furthermore, patient characteristics and outcomes were compared between groups. Results: Among 225, 457 unique cultures 692 were Erta-R, 2, 397 were CRE-1/2, and 222, 368 were CS. Overall rates of CRE-1/2 slightly increased from 0.9% to 1.2% over the study period ( P for trend of < 0.0001) while there was a slight negative trend for Erta-R rates ( P for trend =0.006). Rates of CR by pathogen (Figures 1 and 2) were relatively stable over the study period. Enterobacter cloacae was the most common organism in the Erta-R group and K. pneumoniae was the most common CRE-1/2 pathogen. Differences in patient characteristics were seen between the three groups for race, gender, and comorbidities (Table). Both mortality (Erta-R: 10%, CRE-1/2: 9% vs CS: 4%, respectively) and infection-associated length of stay (Erta-R: 8 days; CRE-1/2: 8 days vs CS: 6 days, respectively) were higher in both Erta-R and CRE 1/2 when compared to CS ( P < 0.001). There were no differences in outcomes between patients with Erta-R and CRE 1/2. Figure 1. Annual rates of CRE (resistance to both classes) by pathogen over the study period Figure 2. Annual rates of CRE (ertapenem R only) by pathogen over the study period Table. Patient demographics and outcomes Conclusion: CRE rates were relatively stable over the study period. Despite low incidence, CRE continue to have significant associations with morbidity and mortality. Interestingly, outcomes were similar in patients with isolates resistant to ertapenem only when compared to isolates resistant to both classes of carbapenems. This might be reflective of novel treatment options available over the study period. Disclosures: Stephen Marcella, MD, Shionogi Inc. (Employee) Hemanth Kanakamedala, BS, Shionogi Inc. (Independent Contractor) Yun Zhou, MS, Shionogi Inc. (Independent Contractor) Bin Cai, MD, PhD, Shionogi Inc. (Employee) Jason M Pogue, PharmD, BCPS, BCIDP, Shionogi Inc. (Advisor or Review Panel member)